ABUNDANCIA, DISTRIBUCION Y ESTACIONALIDAD DE ADULTOS DE LAS ESPECIES COSMOPOLITAS DEL GENERO DROSOPHILA (DIPTERA, DROSOPHILIDAE) EN CHILE - Brncic, Danko (Acta Entomológica Chilena, 2022)
Within the genus Drosopliila ihere are 8 cosmopolitan species: D. ananassae, D. biisckii, D. ¡mmigrans, D. funebris, D. hydei, D. melanogaster, D. repleta and D. simulans. The last 7 ones have been frequently collected in Chile. D. ananassae that is a circuntropical species, has been observed only in two occasions on imported tropical fruits. In spitc that all the cosmopolitan species live closely associated to human activities, ihey show well-cut diffcrenccs regarding distribution, habitat preferences, abundance and seasonal activity.